ICT to serve hajj: analytical study - Hameed, Shihab A. (2010)
Hajj (pilgrimage) is the fifth pillar of Islam that must be carried out at least once in their lifetime by every able-bodied Muslim. It is the largest annual convention of Faith in the world that requires traveling to Mecca. Hajj is performed based on predetermined dates, times, and places. It is a demonstration of the solidarity of the Muslim people, and their submission to Allah the Exalted (GOD). Hajj is an important event in Muslims' life, which offers religious, educational, scientific, social, economical, political and other benefits that are rewarded by Allah SWT to Muslims. Two to three millions out of One and half billion of Muslims around the world, performed Hajj annually. Time, date and place limitations related to Hajj leads to several difficulties and problems that require suitable solutions. Literature review LR, survey, and analysis summarize Hajj difficulties as: Managerial and organizational problems; Lack of information and misunderstanding; and difficulties in dialogue between people, pilgrims and organizational committees. This research paper proposes suitable solutions to solve difficulties using the powerful capabilities of information and communication technologies ICT. It shows the main components of a Comprehensive Hajj Model that includes: comprehensive Hajj database model for managing, organizing and tracking pilgrims and other stakeholders; a Multi- lingual Hajj Educational model on Web-based or CD; and a portable Hajj emergency and guidance model. This comprehensive solution offers: religious, educational, scientific, social, economical, political and other benefits for Muslims. It can be consider as a step toward Muslim unity and offering a unified understanding and cooperation between Muslims.